Ritonavir and Topical Ocular Corticosteroid Induced Cushing's Syndrome in an Adolescent With HIV-1 Infection. Issue 5 (May 2017) - Rainsbury, Paul G.; Sharp, Jessica; Tappin, Alison; Hussey, Martin; Lenko, Alexandra; Foster, Caroline
Abstract : Cushing's syndrome after topical ocular corticosteroid use is extremely rare. We describe a case of symptomatic Cushing's syndrome in an adolescent male with sight-threatening vernal keratoconjunctivitis on antiretroviral therapy for HIV-1 infection that included ritonavir, a potent cytochrome p450 CYP3A4 inhibitor. CYP3A4 inhibition reduces the metabolism of exogenous corticosteroids leading to suppression of endogenous steroid production and Cushing's syndrome.